Phytochemical analysis, antibacterial and cytotoxic efficacy of n -hexane extract from Iraqi cultivated Jatropha integerrima: Isolation of stigmasterol and β-carotene using CombiFlash - Marwa, J M; Nabaa, M I (Plant Science Today, 2025)
Jatropha integerrima a member of the Euphorbiaceae family, is well-known for its numerous secondary metabolites with medicinal applications. This study aims to investigate the phytochemical composition of the n-hexane extract of the aerial parts of J. integerrima grown in Iraq. The work focuses on the identification, separation and characterization of bioactive phytosterols and terpenoids, as well as evaluating the antibacterial activity of the extract against Staphylococcus aureus and Acinetobacter baumannii. Furthermore, the cytotoxic effect of the extract on the B16 melanoma skin cancer cell line was assessed utilizing the 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay. Two chromatographic techniques, thin layer chromatography (TLC) and gas chromatography mass spectrometry (GC-MS), are used to detect chemicals and for fractionation and isolation, CombiFlash chromatography and high performance liquid chromatography (HPLC) were used. Two beneficial compounds, β-carotene and stigmasterol, were successfully isolated. The antibacterial assay revealed that the n-hexane extract exhibited significant efficacy, especially against Gram-positive bacteria (S. aureus) and demonstrated a notable cytotoxic effect with the highest inhibition rate of 84.00 % on the skin cancer (B16) cell line at a 200 μg/mL concentration. The values of the half maximal inhibitory concentration (IC50) of the extract were 29.86 μg/mL. The isolated components were characterized by HPLC, Fourier transform infrared spectroscopy (FTIR) and ultraviolet-visible (UV-Vis) spectroscopy to verify the existence of stigmasterol and β-carotene. Anti-inflammatory, neuroprotective and antioxidant are the most well -known properties of these compounds. As a result, separating and characterizing these compounds from J. integerrima can thus expose significant information on their possible medical use. This study is the first comprehensive analysis of the chemical composition of J. integerrima in Iraq, highlighting its promising medicinal value.